Inclusive education: a question of attitudes of people with disabilities - Dimitrova Radojichikj, Daniela; Chichevska Jovanova, Natasha (My University, 2016)
This study investigated the attitudes of 57 peoples with disability towards including students with disabilities in the regular school. The findings revealed that, in general, peoples with disability showed less positive attitudes towards inclusion, and peoples with physical disability showed more positive attitudes than those with visual or hearing impairment did. Furthermore, participants’ attitudes become negative because of their view of education placement for students with intellectual disabilities, behavioral and emotional disorders to be in the special school.
Keywords: Attitudes, Inclusive education, Peoples with Disabilities, Students with Disabilities